2003
DOI: 10.1073/pnas.2334159100
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Ca 2+ and the phospholipid PIP 2 regulate the taste transduction ion channel TRPM5

Abstract: The transduction of taste is a fundamental process that allows animals to discriminate nutritious from noxious substances. Three taste modalities, bitter, sweet, and amino acid, are mediated by G protein-coupled receptors that signal through a common transduction cascade: activation of phospholipase C ␤2, leading to a breakdown of phosphatidylinositol-4,5-bisphosphate (PIP2) into diacylglycerol and inositol 1,4,5-trisphosphate, which causes release of Ca 2؉ from intracellular stores. The ion channel, TRPM5, is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
367
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 384 publications
(384 citation statements)
references
References 51 publications
13
367
1
Order By: Relevance
“…Could these two channels interact directly? TRPM5 is a Ca 2ϩ -activated channel (40,41), whereas, under physiological conditions, the current flowing through CNGA2 is made up mostly of Ca 2ϩ (42). Intriguingly, the finding that immunoreactivity for TRPM5 is found in small spots with an average diameter of 69 nm suggests that these channels may be clustered in small microdomains.…”
Section: Discussionmentioning
confidence: 99%
“…Could these two channels interact directly? TRPM5 is a Ca 2ϩ -activated channel (40,41), whereas, under physiological conditions, the current flowing through CNGA2 is made up mostly of Ca 2ϩ (42). Intriguingly, the finding that immunoreactivity for TRPM5 is found in small spots with an average diameter of 69 nm suggests that these channels may be clustered in small microdomains.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 Activation of these G protein-coupled receptors results in the digestion of plasma membrane phospholipids into diacylglycerol and inositol triphosphate, which in turn mobilizes intracellular calcium. [38][39][40] Increased intracellular calcium generated in response to tastant binding initiates membrane depolarization and the release of ATP via Calcium homeostasis modulator 1 (CALHM1) ion channels. 41,42 Type II cells also express voltage-gated sodium and potassium channels that mediate the secretion of ATP as a function of action potential firing rate.…”
Section: Taste Bud Anatomy and Physiologymentioning
confidence: 99%
“…Clapham and colleagues (2002) suggested that receptormediated PIP 2 is required to maintain TRPM7 activity, and its breakdown by receptormediated stimulation of phospholipase C (PLC) is responsible for the inhibition TRPM7 they observed when stimulating cells with agonists that couple to PLC. Although several ion channels, including members of the TRPM family [TRPM4 (Zhang et al 2005;Nilius et al 2006), TRPM5 (Liu and Liman 2003), and TRPM8 (Liu and Qin 2005;Rohacs et al 2005)] are subject to PIP 2 -mediated regulation, the case for TRPM7 has not been made without ambiguity. Most of the experiments presented in support of PIP 2 regulation were performed in cells that overexpress TRPM7 or with receptor agonists that can couple to PLC (or both).…”
Section: Regulation By Receptor Stimulationmentioning
confidence: 99%